2014
DOI: 10.1016/j.cellsig.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin 1 modulates mitochondrial function of Stat3

Abstract: Mitochondrial dysfunction in intestinal epithelial cells (IEC) is thought to precede the onset of inflammatory bowel diseases (IBD). Expression of Prohibitin 1 (PHB), a mitochondrial protein required for optimal electron transport chain (ETC) activity, is decreased in mucosal biopsies during active and inactive IBD. In addition to its activities as a transcription factor, Signal Transducer and Activator of Transcription 3 (Stat3) resides in the mitochondria of cells where phosphorylation at S727 is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Complex I of the ETC is a predominant site of PHB binding, resulting in optimal activity of complex I and the respiratory chain. 11,13 Previous studies have shown that TNF α reduces PHB expression in IECs, 32,42 which we also confirm in the current study (Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Complex I of the ETC is a predominant site of PHB binding, resulting in optimal activity of complex I and the respiratory chain. 11,13 Previous studies have shown that TNF α reduces PHB expression in IECs, 32,42 which we also confirm in the current study (Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
“…TNF α significantly increased mitoSOX fluorescence in Caco2-BBE cells, as shown previously. 32,33 Pretreatment with 10 nM FL3 or FL37 prevented TNF α -induced mitochondrial ROS production.…”
Section: Resultsmentioning
confidence: 98%
“…Depending on phosphorylation of residues S727 or Y705, STAT3 can inhibit or promote nuclear gene expression [23]. Recent seminal studies identified a non-transcriptional role of pS727-STAT3 in stimulating mitochondrial bioenergetic function through electron transport chain (ETC) complex I, II and V activity [2426], probably not by binding directly [27], but by binding to prohibitin 1 [28]. STAT3 can also reduce formation of the mitochondrial permeability transition pore, possibly by interacting with cyclophilin D [29], thus maintaining membrane potential necessary for bioenergetic function, as well as preventing release of cytochrome-c, which leads to apoptosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 phosphorylated at serine 727 (Ser727) localizes in mitochondria (Yu et al, 2015). Mitochondrial P-STAT3 Ser is required for optimal electron transport chain (ETC) activity and protects against stress-induced mitochondrial dysfunction (Wegrzyn et al, 2009), such as increasing levels of reactive oxygen species (ROS) (Han et al, 2014). These findings indicate that STAT3 could have diverse roles, from conveying signals to the (1) nuclei by P-STAT3 Tyr to facilitate transcription of target genes such as SOCS3, and (2) mitochondria by P-STAT3 Ser to foster mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%